2006
DOI: 10.1080/13561820600807270
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the Single Assessment Process: Opportunities and challenges

Abstract: 2Implementing the Single Assessment Process: Opportunities and Challenges. AbstractThe Single Assessment Process (SAP) has been introduced as part of the National Service Framework for Older People (DoH 2001) and has major implications for health and social care.The aim of this study was to evaluate a pilot introduction of the Single Assessment Process in the South-East of England. A qualitative case study design incorporating observation and semi-structured interviews were used to collect data.Assessment visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 24 publications
0
43
0
1
Order By: Relevance
“…Whilst it is possible that our findings reflect ‘teething problems’ inherent within the early stages of such initiatives, they do raise serious questions about future implementation and outcomes. In particular, the considerable differences in local policy implementation and practices raise questions about the possibilities of achieving a standard or common approach (Dickinson, 2006; Hudson, 2005b) and this is of huge concern given the government’s current plans to expand ISA, establishing both the database (Contactpoint) and CAF as national standard systems (DfES 2006a,b; 2007). Indeed recent announcements which use the term ‘integrated practice’ (rather than ISA) suggest a wider vision of cultural change.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst it is possible that our findings reflect ‘teething problems’ inherent within the early stages of such initiatives, they do raise serious questions about future implementation and outcomes. In particular, the considerable differences in local policy implementation and practices raise questions about the possibilities of achieving a standard or common approach (Dickinson, 2006; Hudson, 2005b) and this is of huge concern given the government’s current plans to expand ISA, establishing both the database (Contactpoint) and CAF as national standard systems (DfES 2006a,b; 2007). Indeed recent announcements which use the term ‘integrated practice’ (rather than ISA) suggest a wider vision of cultural change.…”
Section: Resultsmentioning
confidence: 99%
“…Implementing change is a complex, non-linear process that requires ownership and support (Dickinson, 2006) and a recent national service development guide suggested that the one thing that would most improve older people's mental health services is strong, effective leadership, across and within all health and social care organizations (Department of Health & Care Services Improvement Partnership, 2005). CMHTs do not sit in a vacuum, and integration within such teams will not be achieved unless the wider service setting is committed to establishing systems and structures that support and facilitate integration on a broader basis (Lingard & Milne, 2004).…”
Section: Integration Across the Health And Social Care Sectorsmentioning
confidence: 99%
“…When the impairment is explicitly addressed, the methodological and measurement consequences are clear and the use of ICF is often considered essential [21]. The need of a rationalisation and convergence of the disability evaluation methodologies and procedures has been recently addressed by different countries following different principles [16,17,[22][23][24][25]. In international literature, two strategies, strongly influenced by the characteristics of the welfare system providing services and benefits, have essentially been followed.…”
Section: Discussionmentioning
confidence: 99%